Developing a holistic personality through leadership training In The UUM Reserve Officer Training Unit (Palapes) - Nur Syazani Nadia Mustafa; Mohd Adib Abd Muin (Penerbit Universiti Kebangsaan Malaysia, 2024)
Universiti Utara Malaysia has a Reserve Officer Training Unit (PALAPES UUM) consisting of three services: the Army, Navy and Air Force. Every cadet officer who undergoes military training at PALAPES UUM is exposed to various knowledge and skills. The PALAPES training program is one of the curriculum courses at UUM that aims to create holistic graduates by requiring all students to excel in soft skills such as leadership, collaboration, communication, and continual learning. This research aims to develop a holistic leadership personality through Palapes training. Each cadet has an Islamic moral code. This article aims to explain some leadership that form the holistic personality of PALAPES UUM cadets; among them are forming time discipline, application ethics, organising tactical strategies, managing weapons, managing emotions and patriotism values. Islamic leadership concepts, on the other hand, have had little impact on the characteristic leadership method. As a result, the research proposes that military commanders be trained with the necessary Islamic knowledge to improve their leadership abilities and decentralise authority and responsibility. The result of this knowledge and skills can help PALAPES UUM cadet officers become skilled and dedicated holistically. Therefore, an in-depth discussion will be discussed in this article. In conclusion, the findings indicated that the military leadership training program has a positive effect and many benefits for cadets.